Numerical Study of The Effect of Penstock Dimensions on a Micro-hydro System using a Computational Fluid Dynamics Approach - Putra, Yoga Satria; Noviani, Evi; Muhardi, Muhardi (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The performance of a micro-hydro system needs always to be improved so that the electrical power produced can be more optimal. This article aims to study numerically the effect of penstock dimensions on the potential of electrical energy in a micro-hydro system using a computational fluid dynamics (CFD) approach. The study of the effect of dimensions on the performance of a hydropower system is still quite rare. In this paper, the impact of dimensions on the micro-hydro system has been analysed by constructing thirty simulations of water flow in the penstock consisting of five variations of penstock slope ( and ) for six penstock diameter variations ( m, m, m, m, m, and m). The simulation was built using the open-source CFD software OpenFOAM which applies the finite volume method to solve the Navier-Stokes equation as a flow model. The simulated water velocity profile is then validated against the velocity profile of the analytical solution (power-law) for turbulent flow in the pipe. Energy loss analysis on the penstock has been carried out to determine the cause of the energy loss in the penstock characterised by loss coefficient . An enormous value will impact the decrease in the electric power potential of a micro-hydro system. The total length of the penstock induces the variation of the which affects the changes in the electrical power of the micro-hydro system. The shorter will increase the electric power potential of a micro-hydro system. With a high flow velocity of water in the penstock ( m/s), the electric power increases linearly with increasing the diameter value of the penstock. The analysis results show that the penstock dimensions can affect the changes in the electric power of the micro-hydro system. In addition, the work presented in this article has shown that the CFD approach can be used as a low-cost initial step in building an actual micro-hydro system